Mucocele of lower lip: case report and literature review / Dayang Fadzlina Abang Ibrahim ... [et al.] - Abang Ibrahim, Dayang Fadzlina; Zainuren, Zalikha Adila; Venkiteswaran, Annapurny; Wan Ahmad Kamil, Wan Hazirah (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
Mucocele is a common pathological lesion in the oral cavity occurring due to obstruction of the salivary gland. The diagnosis is mainly clinical due to its pathognomonic presentation, but it has to be confirmed with histopathological analysis for a definitive diagnosis. A 12-year-old boy went to the Paediatric dental specialist clinic with a chief complaint of a swelling on the left side of the lower lip for about seven months. The aetiological factor was due to trauma secondary to malalignment of an upper canine. The definitive diagnosis was confirmed histologically. The treatment involved surgical resection of the affected tissue, and no recurrence was observed after the surgical procedure. Mucocele is a common soft tissue lesion in the oral cavity and can be successfully resolved via a conventional surgical approach.